2020
DOI: 10.3389/fonc.2020.586603
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Tumor Deposits in Predicting the Efficacy of Chemotherapy in Stage III Colon Cancer

Abstract: Purpose To evaluate the role of tumor deposits (TDs) in predicting the efficacy of chemotherapy in stage III colon cancer. Methods Using the SEER ∗ Stat software Version 8.3.6, we started with a national cohort of colon cancer cases diagnosed between 2004 and 2016. We used the χ 2 (Chi-square) test to compare differences between different categorical variables according to the number of TDs. The Cox proportional haza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…Substantial evidence has shown that TDs are correlated with increased local recurrence and distant metastasis and impaired DFS and OS (10,11,30). Delattre et al (2) found that postoperative chemotherapy would benefit patients with TDs, which was also validated by Shi et al (31). As one of the most common modalities, postoperative RT also plays an important role in the postoperative management of rectal cancer, especially for those who do not receive preoperative RT.…”
Section: Discussionmentioning
confidence: 92%
“…Substantial evidence has shown that TDs are correlated with increased local recurrence and distant metastasis and impaired DFS and OS (10,11,30). Delattre et al (2) found that postoperative chemotherapy would benefit patients with TDs, which was also validated by Shi et al (31). As one of the most common modalities, postoperative RT also plays an important role in the postoperative management of rectal cancer, especially for those who do not receive preoperative RT.…”
Section: Discussionmentioning
confidence: 92%
“…The effect of chemotherapy on CRC patients with TD was inconsistent in previous studies. Shi et al found that the presence of TD and its number did not affect the benefit of chemotherapy in stage III CRC ( 39 ), while Li et al reported that patients with TD did not display a disease-free survival (DFS) benefit from chemotherapy ( 40 ). However, in our study, for the postoperative CRC-NDM patients with TD, chemotherapy (SHR = 0.542, 95% CI: 0.501–0.586) was independently associated with a favorable prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…The survival benefit of chemotherapy in patients with colorectal cancer with TD has been inconsistent in previous studies because it was not clear whether the pN1c category was or was not equal to LNM ( 9 ). It was reported that the presence and number of TDs did not affect the benefit of chemotherapy in stage III colorectal cancer ( 22 ). It has also been shown that patients with TD did not show a benefit in disease-free survival following chemotherapy ( 23 ).…”
Section: Discussionmentioning
confidence: 99%